SWI/SNF tumor suppressor gene PBRM1/BAF180 in human clear cell kidney cancer - Amrita M. Nargund; Hatice U. Osmanbeyoglu; Emily H. Cheng; James J. Hsieh (Molecular & Cellular Oncology, 2017)
Mutations within chromatin modulating protein complexes have dominated the novel cancer gene landscape. However, little is known about how individual aberrations contribute to cancer formation. A novel Pbrm1 kidney cancer mouse model examining the role of Pbrm1 provides much needed clue concerning how SWI/SNF complexes might function as tumor suppressors.